2017
DOI: 10.5350/dajpn2017300408
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body mass index on the sexual functions of morbidly obese female patients

Abstract: The effect of body mass index on the sexual functions of morbidly obese female patientsObjective: The aim of this study is to investigate whether morbidly obese female patients are suffering sexual dysfunction, in addition to analyzing the effect of body mass index (BMI) on sexual functions. Method: A total of 72 morbidly obese women admitted to the Endocrinology Department, whose BMI scores were 40 or over, and 28 healthy women age-matched with the morbidly obese group, whose BMI scores were under 30 were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In our study, while the ASEX total score and arousal sub‐scale score decreased significantly in patients who switched to PP3M ( p = 0.015; p = 0.020, respectively), there was no significant change in other sub‐scales. Previously in the literature, it has been reported that there is a positive correlation between body mass index and ASEX scores (Gonenir Erbay et al., 2017; Kolotkin et al., 2006; SA. M. A. Smith et al., 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, while the ASEX total score and arousal sub‐scale score decreased significantly in patients who switched to PP3M ( p = 0.015; p = 0.020, respectively), there was no significant change in other sub‐scales. Previously in the literature, it has been reported that there is a positive correlation between body mass index and ASEX scores (Gonenir Erbay et al., 2017; Kolotkin et al., 2006; SA. M. A. Smith et al., 2012).…”
Section: Discussionmentioning
confidence: 96%
“…(p = 0.015; p = 0.020, respectively), there was no significant change in other sub-scales. Previously in the literature, it has been reported that there is a positive correlation between body mass index and ASEX scores (Gonenir Erbay et al, 2017;Kolotkin et al, 2006; SA. M.…”
Section: Montalvo Et Al Reported That Prolactin Level Decreased Aftermentioning
confidence: 90%
“…Morbidly obese patients had more sexual dysfunctions compared to the normal-weight women. 16 Rowland et al 17 expressed that obesity can affect the sexual response. In the study conducted by Cherick 14 , it was stated that when obese individuals lost weight, they had an increased self-esteem and an enhanced sexual quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study as BMI increases, the quality of sexual life decreases. Morbidly obese patients had more sexual dysfunctions compared to the normal‐weight women 16 . Rowland et al 17 expressed that obesity can affect the sexual response.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a BMI ≥40 were defined as morbid obese. [16] The starting point of the sacroiliac joint was used to determine the levels of ureteral stones. The ureteral stones under this determined point were accepted as distal ureteral stones.…”
Section: Methodsmentioning
confidence: 99%